2002
DOI: 10.1086/341662
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nephrotoxicity of Conventional Amphotericin B Therapy after Minimal Nephroprotective Measures: Animal Experiments and Clinical Study

Abstract: Amphotericin B (AmB)-treated rats develop severe polyuria, polydypsia, impairment of renal concentrating ability, and morphologic signs of tubular damage. However, renal insufficiency develops quickly only in animals in which water intake is restricted to the median volume drunk by rats of the control group. Therefore, vigorous hydration seems crucial for prevention of AmB-induced nephrotoxicity. In a clinical study, 61 patients with hematologic malignancies receiving AmB therapy were massively hydrated to ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 42 publications
2
56
0
2
Order By: Relevance
“…Volume expansion might also mitigate the nephrotoxicities of filtered urate [22][23][24] and hemoglobin 25 and of Shiga toxin's effects on renal tubular epithelial cells 26 and monocytes 27 that are independent of thrombotic changes. Indeed, salt loading protects against presumably nonthrombotic nephrotoxicity, such as that caused by amphotericin, 28 and isotonic saline prevents nephropathy caused by radiocontrast media better than does hypotonic saline. 29 It is interesting that unlike a Minnesota study that suggested that antibiotic administration was related to a milder course of HUS, 30 we detected no statistically significant association between antibiotic administration and development of either oligoanuria or nonoligoanuria.…”
Section: Discussionmentioning
confidence: 99%
“…Volume expansion might also mitigate the nephrotoxicities of filtered urate [22][23][24] and hemoglobin 25 and of Shiga toxin's effects on renal tubular epithelial cells 26 and monocytes 27 that are independent of thrombotic changes. Indeed, salt loading protects against presumably nonthrombotic nephrotoxicity, such as that caused by amphotericin, 28 and isotonic saline prevents nephropathy caused by radiocontrast media better than does hypotonic saline. 29 It is interesting that unlike a Minnesota study that suggested that antibiotic administration was related to a milder course of HUS, 30 we detected no statistically significant association between antibiotic administration and development of either oligoanuria or nonoligoanuria.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental data from the last decade point to an important effect of saline loading on the prevention of the loss of renal function in individuals treated with AmphoB. In two trials, there was no significant loss of renal function in sodium chloride-loaded patients [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies published during the last two decades have shown that nephrotoxicity can be prevented by the use of sodium loading [4,[7][8][9][10][11], slowing drug infusion [12] and through the use of liposomal or lipid-complex amphotericins [13][14][15][16][17].…”
mentioning
confidence: 99%
“…The mechanism that generates toxicity is associated with dysfunction in the renal blood flow resulting in the direct structural lesion in tubule cells, reduction in glomerular filtration rate and, consequently, electrolyte disturbances and acid-base imbalance (Mayer et al, 2002). Thus, the main manifestations of nephrotoxicity are a reduction of glomerular filtration and hypokalemia and hypomagnesemia caused by direct tubular lesion; nephrocalcinosis and renal tubular acidosis might also occur (Klepser, 2011;Longuet et al, 1991).…”
Section: Chronic Side Effects Nephrotoxicitymentioning
confidence: 99%